Effect of Hydrogen Bond on the n(CºN) Stretching Mode of Acetonitrile in the Binary Mixture (Acetonitrile + Water): A Combined Raman Spectroscopy and Theoretical Study - Ou-Yang, Shun-Li; Zhang, Xue-Feng; Liu, Jing-Yao; Li, Zuo-Wei; Wu, Nan-Nan; Tian, Yan-Yie (Asian Journal of Chemistry, 2013)
Hydrogen bond in the binary mixture system of acetonitrile and water has been studied by using experimental Raman spectroscopy and quantum chemical theoretical calculations. Experimentally, the n(CºN) as a marker bond for the degree of hydrogen bond in this binary mixture (acetonitrile + water) has been monitored by Raman spectroscopy. Theoretically, the optimized structures, vibrational frequencies and stabilization energies of the neat acetontrile and the hydrogen-bonded CH3CN…HOH complexes are calculated at the B3LYP/6-311 + G(d,p), MP2/6-311+G(d,p) and CCSD/6-311+G(d,p) levels of theory, respectively. The results show that the wavenumber position of the CºN stretching mode is shifted to higher wavenumber due to the hydrogen bond and the change in the line width (full width half maximum, FWHM) have been explained for neat as well as binary mixtures with different concentrations, in terms of the concentration fluctuation and the microviscosity.